2014
DOI: 10.4269/ajtmh.13-0621
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial Transmission of Vaccinia virus during a Bovine Vaccinia Outbreak in Brazil: A New Insight in Viral Transmission Chain

Abstract: Abstract. Bovine vaccinia (BV) is an emerging zoonosis caused by the Vaccinia virus (VACV), genus Orthopoxvirus (OPV), Poxviridae family. In general, human cases are related to direct contact with sick cattle but there is a lack of information about human-to-human transmission of VACV during BV outbreaks. In this study, we epidemiologically and molecularly show a case of VACV transmission between humans in Sã o Francisco de Itabapoana County, Rio de Janeiro state. Our group collected samples from the patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…A recent study evaluated the knowledge of healthcare professionals from a BV endemic area, and confirmed that 43.1% of participants were unaware of BV and aspects related to zoonotic VACV infections [ 94 ]. A common theme in the literature is that person-to-person VACV transmission can easily occur due to the direct contact with individuals recently vaccinated against smallpox [ 102 , 103 , 104 , 105 , 106 , 107 ], and direct contact with individuals naturally infected with zoonotic VACV [ 93 , 104 , 108 ]. Hence, person-to-person transmission should not be neglected during zoonotic BV outbreaks as infected individuals could act as possible sources of infection for healthcare professionals, increasing the burden to public health [ 94 ].…”
Section: The Bad: the Economic And Public Health Burden Associatedmentioning
confidence: 99%
“…A recent study evaluated the knowledge of healthcare professionals from a BV endemic area, and confirmed that 43.1% of participants were unaware of BV and aspects related to zoonotic VACV infections [ 94 ]. A common theme in the literature is that person-to-person VACV transmission can easily occur due to the direct contact with individuals recently vaccinated against smallpox [ 102 , 103 , 104 , 105 , 106 , 107 ], and direct contact with individuals naturally infected with zoonotic VACV [ 93 , 104 , 108 ]. Hence, person-to-person transmission should not be neglected during zoonotic BV outbreaks as infected individuals could act as possible sources of infection for healthcare professionals, increasing the burden to public health [ 94 ].…”
Section: The Bad: the Economic And Public Health Burden Associatedmentioning
confidence: 99%
“…During outbreaks, direct contact with infected animals is the main transmission route to humans, but it may also occur by contact with contaminated fomites. Furthermore, reports have suggested a possible human-to-human transmission of VACV [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although raw milk and cheese are potential sources of infection, no clinical cases have been associated with this transmission route ( 3 , 4 ). Data for person-to-person transmission in Brazil are scarce, but person-to-person transmission was recently reported ( 5 ). We report a possible case of person-to-person transmission of VACV.…”
mentioning
confidence: 99%
“…On the basis of previous studies that detected viral DNA in clinical samples from persons with bovine vaccinia ( 1 ), we used a quantitative PCR to amplify the vgf and ha genes of VACV ( 3 5 ), a standard PCR to detect the ha gene ( 3 5 ), and a seminested PCR to detect the ati gene (F.L. Assis, unpub.…”
mentioning
confidence: 99%